1983
DOI: 10.1055/s-2007-1021537
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Alterations of the Esophagus after Endoscopic Sclerotherapy of Varices

Abstract: With the combined peri- and intravascular sclerosing technique esophageal varices can be completely eliminated in an average of three treatment sessions. In order to check the success of the procedure, endoscopic and histological findings at the various stages of treatment after sclerosing with 1% Polidocanol were compared. Clinical and autopsy findings are in agreement. After sclerosing, necroses of the mucosa and intramural inflammations occur regularly in the first week. The varices are thrombosed. Later, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1984
1984
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Both decreased distal esophageal sphincter pressure and abnormal peristaltic waves in the esophagus have been reported [4,8,10,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both decreased distal esophageal sphincter pressure and abnormal peristaltic waves in the esophagus have been reported [4,8,10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal strictures may require dilatation. Besides this, there may also be motility disturbances of the esophagus [4,7,10,14]. The incidence and severity of these disturbances vary in different reports.…”
mentioning
confidence: 99%
“…We carried out a clinical study on 15 patients (9 males and 6 females; average age, 45 + 12 years) with liver cirrhosis categorized as Child A and endoscopic evidence of degree II-IV esophageal varices with red spots but no history of bleeding [1,3,7,15,16].…”
Section: Methodsmentioning
confidence: 99%
“…Soehendra et al [50] observed mild esophageal stenosis in 33 of 414 patients (8%) following combined paravariceal and intravariceal injection with polidocanol. Us ing the same sclerosant and a paravariceal technique, Kjaergaard et al [54] reported strictures in 13 of 61 patients (21%).…”
Section: Complications Of Injection Sclerotherapymentioning
confidence: 99%
“…Intravariceal injec tion is favored by most endoscopists al though some advocate the paravariceal tech nique [43][44][45][46][47][48]. Concomitant use of both methods has been described [41,49,50]. The limited data available suggest that intravari ceal injection may be the preferred technique.…”
Section: Techniques Of Endoscopic Sclerotherapymentioning
confidence: 99%